2014
DOI: 10.1002/cncr.28355
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of therapeutic music video intervention for resilience outcomes in adolescents/young adults undergoing hematopoietic stem cell transplant: A report from the Children's Oncology Group

Abstract: Background To reduce the risk of adjustment problems associated with Hematopoietic Stem Cell Transplant (HSCT) for adolescents/young adults (AYA), we examined efficacy of a therapeutic music video (TMV) intervention delivered during the acute phase of HSCT to: (a) increase protective factors of spiritual perspective, social integration, family environment, courageous coping, and hope-derived meaning; (b) decrease risk factors of illness-related distress and defensive coping; and (c) increase outcomes of self-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
167
0
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(188 citation statements)
references
References 40 publications
5
167
0
16
Order By: Relevance
“…So it is compatible with the results achieved in previous studies on the effect of music therapy in improving psychological function and resolve of some psychiatric disorders including anxiety and improve stress management [7] [10] [11] [16]- [20]. The effect music therapy on social growth may be due to mood regulation [6]- [8] or by improving function of brain in coping with stress, self-satisfaction and self-confidence increases [13]- [15]. As music induces safe environment for good social relationship, it may cause positive self-esteem and increases social approach and interests [16]- [19].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…So it is compatible with the results achieved in previous studies on the effect of music therapy in improving psychological function and resolve of some psychiatric disorders including anxiety and improve stress management [7] [10] [11] [16]- [20]. The effect music therapy on social growth may be due to mood regulation [6]- [8] or by improving function of brain in coping with stress, self-satisfaction and self-confidence increases [13]- [15]. As music induces safe environment for good social relationship, it may cause positive self-esteem and increases social approach and interests [16]- [19].…”
Section: Discussionsupporting
confidence: 80%
“…Some studies revealed that music has positive impact on human behaviors and mood [6]- [8]. Therefore music has been used for treatment of medical and psychiatric disorders [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…A trend for an increased quality of life was observed in the intervention group. This feasibility study was the pilot for the study of Robb et al [44]. Here, the same study design was used to further investigate primary (e.g.…”
Section: Technology-based Interventionsmentioning
confidence: 99%
“…Six studies [39][40][41][42][43][44] examined the effects of technologybased interventions. The majority of these studies used multiple outcome parameters.…”
Section: Technology-based Interventionsmentioning
confidence: 99%
“…Nevertheless, prior studies focused primarily in the use of music therapy to minimize pain associated with short medical procedures such as venipuncture but not for the treatment of post-surgical pain [9][10][11]. The distracting and anxiolytic properties of audiobooks may also have a promising effect on pain control in children undergoing surgery but their efficacy remains to be evaluated [12]. Currently, there is a lack of recommendation for non-pharmacological strategies by practice guidelines for the treatment of post-surgical pain in children [13].…”
Section: Introductionmentioning
confidence: 97%